Proinflammatory and anti-inflammatory cytokine changes related to menopause - Malutan, Andrei Mihai; Dan, Mihu; Nicolae, Costin; Carmen, Mihu (Menopause Review/Przegląd Menopauzalny, 2014)
The aim of the study was to determine menopause-related changes in serum levels of main proinflammatory and anti-inflammatory cytokines. Material and methods: The study included 175 women, who were divided into 5 study groups (group 1 – fertile women; group 2 – pre- and perimenopausal women; group 3 – postmenopausal women; group 4 – surgically induced menopausal women; group 5 – women with chronic inflammatory pathology). We evaluated the serum levels of interleukin (IL)-1α, IL-1β, IL-2, IL-4, IL-5, IL-6, IL-8, IL-10, IL-17, IL-20 and of the tumour necrosis factor (TNF)α with the use of two multiplex cytokine kits. We also determined the serum levels of follicle stimulating hormone (FSH), luteinizing hormone (LH), 17β-estradiol (17β-E2), progesterone (P), dehydroepiandrosterone (DHEA) and dehydroepiandrosterone sulfate (DHEAS) using sandwich ELISA. Results : The serum level of IL-1β, IL-8 and TNF-α in women with natural menopause and in women with surgically induced menopause is significantly higher than in fertile women in the control group. In patients with surgically induced menopause and in women with natural menopause, IL-8 serum levels are similar to those seen in patients with chronic inflammatory diseases. There is a statistically significant decrease in serum levels of IL-20 in women with natural or surgical menopause than in fertile and premenopausal women. Conclusions : Women in menopause have elevated levels of the key proinflammatory cytokines, i.e. IL-1β, IL-8 and TNF-α and low serum levels of IL-20 in comparison with fertile women.